Hypotension prediction index decision support system: a new model for decision support in hemodynamic management - Valbuena-Bueno, Miguel A.; Ripollés-Melchor, Javier; Ruiz-Escobar, Alicia; Fernández-Valdes-Bango, Paula; Lorente, Juan V.; Abad-Gurumeta, Alfredo; Monge-García, M. Ignacio (Frontiers in Anesthesiology, 2024)
Intraoperative hypotension (IOH) poses significant risks during surgeries, necessitating effective management for patient safety and successful outcomes. The Hypotension Prediction Index (HPI) software has been developed as a model for decision support, assisting anesthesiologists in monitoring and addressing hypotensive episodes during non-cardiac surgeries. Based on the predictive capabilities of HPI, as well as the physiological variables offered by the Hemosphere monitor, we have created a Decision support system (HPI-DSS) for hemodynamic management. This article provides a comprehensive overview of the HPI-DSS with a focus on its model for hemodynamic decision support. The methodology, results, and limitations are discussed, along with potential applications and suggestions for further research.